2008
DOI: 10.1016/j.comnet.2007.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Scheduling bulk file transfers with start and end times

Abstract: The advancement of optical networking technologies has enabled e-science applications that often require transport of large volumes of scientific data. In support of such data-intensive applications, we develop and evaluate control plane algorithms for scheduling bulk file transfers, where each transfer has a start time and an end time. We formulate the scheduling problem as a special type of the multi-commodity flow problem. To cope with the start and end time constraints of the file-transfer jobs, we divide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…If the time budget for tree computation is chosen to be very short, e.g., close to the round-trip propagation time, we may restrict each multicast session to use a small number of precomputed trees (e.g., 4 -100 trees); finding the min-cost tree among them is trivial. Experiences have shown that the loss in throughput due to the restriction on the trees is likely to be small (see [38] for the unicast case). The performance guarantees found in the paper still apply if we modify the optimization problem by adding the constraints about the allowed trees.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…If the time budget for tree computation is chosen to be very short, e.g., close to the round-trip propagation time, we may restrict each multicast session to use a small number of precomputed trees (e.g., 4 -100 trees); finding the min-cost tree among them is trivial. Experiences have shown that the loss in throughput due to the restriction on the trees is likely to be small (see [38] for the unicast case). The performance guarantees found in the paper still apply if we modify the optimization problem by adding the constraints about the allowed trees.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Data transfer scheduling with a specific start time and a particular deadline has been studied in [34,38,35]. The scheduling problem has been formulated as a multicommodity flow problem, and uniform time slices have been used to model the time dependency in [35].…”
Section: Related Workmentioning
confidence: 99%
“…The scheduling problem has been formulated as a multicommodity flow problem, and uniform time slices have been used to model the time dependency in [35]. The objective is to maximize the total transfer throughput, and data transfers can use varying bandwidth in every time slice.…”
Section: Related Workmentioning
confidence: 99%
“…Data transfer scheduling with a specific start time and a particular deadline has been studied in [39,47,42]. The scheduling problem has been formulated as a multi-commodity flow problem, and uniform time slices have been used to model the time dependency in [42].…”
Section: Time and Resource Conflictsmentioning
confidence: 99%
“…The scheduling problem has been formulated as a multi-commodity flow problem, and uniform time slices have been used to model the time dependency in [42]. The objective is to maximize the total transfer throughput and data transfers can use varying bandwidth in every time slice.…”
Section: Time and Resource Conflictsmentioning
confidence: 99%